El último kantiano - Leonardo Tovar González (Theoría Revista del Colegio de Filosofía, 2007)
According to Foucault, Kant established the mission of philosophizing as ontology of the present, however when applying the lessons to our era everything seems to indicate that we should abandon his announcements full of hope on the gradual moral and political illustration of human kind and conclude, with Benjamin, after the memory of the defeated that “every act of civilization is an act of barbarity”. Or perhaps the distance between the rationalist scatology of the philosopher of Könisgsberg and the agonistic memorial of the thinker of Berlin is not so large, since in both cases they intend to replevy human dignity, in Kant for the sake of making it possible, in Benjamin for the indignity not to be repeated.